2011
DOI: 10.1039/c1nr10274e
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and microwave-absorbing properties of magnetic nickel ferrite nanocrystals

Abstract: The electromagnetic and microwave absorbing properties of nickel ferrite nanocrystals were investigated for the first time. There were two frequencies corresponding to the maximum reflection loss in a wide thickness range from 3.0 to 5.0 mm, which may be bought by the nanosize effect and the good crystallization of the nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(107 citation statements)
references
References 18 publications
1
103
0
3
Order By: Relevance
“…Material magnetik ferit berstruktur kristal kubik dengan formula umum MFe 2 O 4 (M = Ni, Co,Mn, Zn, Mg, Fe,dsb) merupakan kandidat bahan magnetik yang tepat untuk pemanfaatan bahan absorber dikarenakan fleksibilitas pemanfaatan dan performa elektromagnetik yang tinggi pada rentang frekuensi yang luas [2] . Di antara grup ferit berstruktur kristal AFe 2 O 4 ini, Nikel ferit (NiFe 2 O 4 ) merupakan salah satu yang sangat menarik untuk dikembangkan dikarenakan memiliki struktur magnetik yang unik, kestabilan fasa yang baik, dan nilai magnetisasi saturasi yang tinggi [3] .…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Material magnetik ferit berstruktur kristal kubik dengan formula umum MFe 2 O 4 (M = Ni, Co,Mn, Zn, Mg, Fe,dsb) merupakan kandidat bahan magnetik yang tepat untuk pemanfaatan bahan absorber dikarenakan fleksibilitas pemanfaatan dan performa elektromagnetik yang tinggi pada rentang frekuensi yang luas [2] . Di antara grup ferit berstruktur kristal AFe 2 O 4 ini, Nikel ferit (NiFe 2 O 4 ) merupakan salah satu yang sangat menarik untuk dikembangkan dikarenakan memiliki struktur magnetik yang unik, kestabilan fasa yang baik, dan nilai magnetisasi saturasi yang tinggi [3] .…”
Section: Pendahuluanunclassified
“…Hal ini disebabkan oleh tingkat homogenitas fasa penyusun yang lebih rendah dan dapat pula disebabkan oleh tidak meratanya sebaran distribusi kation pada saat pembentukan fasa. Bagaimanapun, nilai kristalit komposit yang dihasilkan pada seluruh material komposit jika dibandingkan dengan ukuran kristalit fasa NiFe 2 . Ini dikarenakan difusi antar butir pada masingmasing fasa saat proses milling sehingga menyebabkan batas butir mengembang dan membuat nilai kristalit menjadi lebih besar dibandingkan fasa utama yang dibuat secara mandiri [17] .…”
Section: Prosedur Percobaanunclassified
See 1 more Smart Citation
“…Magnetic absorbers belong to the class of magnetic loss materials including ferrites, metals Fe, Co, Ni and carbonyl iron [6][7][8][9]. Ferrites, including soft magnetic and hard magnetic ferrites are better candidates for absorbing materials because of the high magnetic loss, though their dielectric loss has never been neglected, and have been intensively investigated [10][11][12]. Currently, the research interest in ferrite materials is to enhance the absorption intensity and broaden absorption bandwidth under −10 dB in the microwave band by doping [13][14][15] and controlling particle morphology and size [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] As is known, the high-performance EM microwave absorption materials should satisfy the requirements of the strong absorption, wide frequency band, thin thickness, light weight and high thermal stability. 8,9 It has been reported that the graphene oxide (GO) sheets exhibit superior electrical conductivity, large surface area and excellent structural flexibility, 10 which can be combined with various magnetic nanoparticles to form carbon-based composite nanostructures 11 with good microwave absorbing properties resulting from their magnetic and dielectric components.…”
Section: Introductionmentioning
confidence: 99%